Photobiomodulation (λ=808nm) and PlateletRich Plasma (PRP) for the Treatment of Acute Rheumatoid Arthritis in Wistar Rats: PBM and PRP in Arthritis - Gonçalves, Amanda Bezerra; Bovo, Júlia Leme; Gomes, Bruna Silva; Pigoso, Acácio Antonio; Felonato, MaÃra; Esquisatto, Marcelo Augusto Marreto; Lopes Filho, Gaspar de Jesus; Bomfim, Fernando Russo Costa (Journal of Lasers in Medical Sciences, 2021)
Introduction: Rheumatoid arthritis (RA) causes inflammation, pain, edema, and articular degradation and its treatment can be based on anti-inflammatory drugs, photobiomodulation (PBM) and/or platelet-rich plasma (PRP) that can decrease cell flow and promote local healing. In the present study, we evaluate the effects of PBM and PRP on acute arthritis in Wistar rats through inflammatory and oxidative stress parameters. Methods: Thirty female Wistar rats were assigned to five groups (n=6, each group): Control, Sham, PRP, Laser, and PRP+Laser. For arthritis induction, all animals of groups Sham, PRP, Laser and PRP+Laser received an intraarticular injection of Zymosan® (200µg) in the right knee. Twenty-four hours post-arthritis induction, PRP was prepared and injected (8 × 105 of platelets) in animals of PRP and PRP+Laser groups. PBM was performed in Laser and PRP+Laser groups by single-dose therapy with the GaAlAs laser (λ=808 nm, P=25 mW, fluence=30 J/cm2, beam area=0.02 mm2, t=33 seconds, E=0.825 J, punctual application). After seven days of induction, serum samples were collected and thiobarbituric acid reactive substances (TBARS), nitric oxide (NO), and catalase activity were analyzed. Morphological parameters were measured for inflammation areas, cartilage thickness, and C3 protein expression in knee samples. Statistical analysis was performed with an ANOVA test and Tukey’s posthoc test with a significance level of 5% (P<0.05). Results: NO was lower in the treated groups compared to the Sham group, and TBARS did not show any differences, while catalase showed greater activity between PRP+Laser versus PRP (P<0.05). Inflammatory areas and cartilage thickness were lower in the treated groups compared to Sham (P<0.05), while no differences in C3 protein expression were observed. Conclusion: PBM associated with PRP is better for anti-inflammatory and joint preservation by morphological aspects and NO levels that concern a potential clinical application. DOI: 10.34172/jlms.2021.60